The flying trunk and other stories from Hans Andersen - Lewis, Naomi; Andersen, H. C. 1805-1875. (Hans Christian) (New York Prentice-Hall Books for Young Readers, 1986)
Retells thirteen fairy tales by the Danish author, including "The Tinderbox," "The Steadfast Tin Soldier," "The Little Match Girl," and "The Snowman."
Keywords: Fairy tales -- Denmark; Children's stories, Danish -- Translations into English; Fairy tales; Short stories